2015
DOI: 10.1016/j.disc.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Edge-colorings of uniform hypergraphs avoiding monochromatic matchings

Abstract: a b s t r a c tFor positive integers k, ℓ and r, and an r-uniform hypergraph H, let c k,ℓ,r (H) be the number of k-colorings of the set of hyperedges of H with no ℓ independent hyperedges of the same color. Let H n,r denote the set of all n-vertex r-uniform hypergraphs and consider the function c k,ℓ,r (n) = max {c k,ℓ,r (H): H ∈ H n,r }, the maximum of c k,ℓ,r (H) over all r-uniform hypergraphs H on n vertices. In this paper, we determine, for all fixed values of r, k and ℓ, and large n, the r-uniform n-verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…When t ≥ 2, one still has to specify which t-stars to take, as there are non-isomorphic choices, and Hoppen, Kohayakawa and Lefmann gave a precise description of the optimal families. Some stability results were also obtained, and in a later paper [19], the same authors consider the problem where one does not forbid monochromatic disjoint pairs, but rather matchings of larger size.…”
Section: Erdős-rothschild For Intersecting Familiesmentioning
confidence: 91%
“…When t ≥ 2, one still has to specify which t-stars to take, as there are non-isomorphic choices, and Hoppen, Kohayakawa and Lefmann gave a precise description of the optimal families. Some stability results were also obtained, and in a later paper [19], the same authors consider the problem where one does not forbid monochromatic disjoint pairs, but rather matchings of larger size.…”
Section: Erdős-rothschild For Intersecting Familiesmentioning
confidence: 91%
“…Lefmann, Person, Rödl and Schacht [19] studied the problem in the setting of three-uniform hypergraphs, with monochromatic copies of the Fano plane forbidden, before Lefmann, Person and Schacht [20] considered arbitrary k-uniform hypergraphs. Further results along this line of research can be found in [12,13,14,18]. Moving the problem into the domain of extremal set theory, Hoppen, Kohayakawa and Lefmann [15] solved the Erdős-Rothschild extension of the famous Erdős-Ko-Rado Theorem [9].…”
Section: Erdős-rothschild Problemsmentioning
confidence: 99%
“…Determining the extremal configurations in general for k ≥ 2 and r ≥ 4 turned out to be a difficult problem. For further results along this line of research (when F is a non-complete graph or a hypergraph), we refer to [16,18,19,26,27,28].…”
Section: Erdős-rothschild Problems In Various Settingsmentioning
confidence: 99%